Drinking motives moderate the impact of pre‐drinking on heavy drinking on a given evening and related adverse consequences—an event‐level study. (5th July 2013) - Kuntsche, Emmanuel; Labhart, Florian
Abstract: Aims: To test whether (i) drinking motives predict the frequency of pre‐drinking (i.e. alcohol consumption before going out); (ii) drinking motives predict HDGE (heavy drinking on a given evening: 4+ for women, 5+ for men) and related adverse consequences (hangover, injuries, blackouts, etc.), even when pre‐drinking is accounted for, and (iii) drinking motives moderate the impact of pre‐drinking on HDGE and consequences. Design: Using the internet‐based cellphone‐optimized assessment technique (ICAT), participants completed a series of cellphone questionnaires every Thursday, Friday and Saturday evening over 5 weeks. Setting: French‐speaking Switzerland. Participants: A total of 183 young adults [53% female, mean age (standard deviation) = 23.1 (3.1)] who completed 7828 questionnaires on 1441 evenings. Measurements: Drinking motives assessed at baseline, alcohol consumption assessed at 8 p.m., 9 p.m., 10 p.m., 11 p.m. and midnight and consequences assessed at 11 a.m. the next day. Findings: Gender‐separate multi‐level models revealed that pre‐drinking predicted HDGE (men: B = 2.17, P  < 0.001; women: B = 2.12, P  < 0.001) and alcohol‐related consequences (men: B = 0.24, P  < 0.01; women: B = 0.29, P  < 0.001). Enhancement motives were found to predict HDGE (B = 0.48, P  < 0.05) and related consequences (B = 0.09, P  < 0.05) among men, while among women coping motives had the same effect (HDGE: B = 0.73, P  < 0.001; consequences: B = 0.13, P  < 0.01). With the exception of conformity motives among women (B = 0.54, P  < 0.05), however, no drinking motive dimension predicted the frequency of pre‐drinking, while coping and conformity motives moderated the impact of pre‐drinking on HDGE (men, conformity: B = −1.57, P  < 0.05) and its consequences (men, coping: B = −0.46, P  < 0.01; women, coping: B = 0.76, P  < 0.05). Conclusions: Among young adults in Switzerland, heavy weekend drinking and the related consequences seem to result from the combination of pre‐drinking, level of negative reinforcement drinking for women and positive reinforcement drinking for men.